Pengaruh Kompetensi Aparatur, Komitmen Organisasi, Transparansi dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Dana Desa - Fitra, Halkadri; Syofyan, Erfrizal; Masdupi, Erni; Mulyani, Erly; Taqwa, Salma; Halmawati, Halmawati (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the influence of apparatus competency, organizational commitment, transparency and community participation on accountability in managing village funds in Agam Regency, West Sumatra Province. This type of research is quantitative research, with data collection using primary data, namely distributing questionnaires to respondents. The research population was heads of village financial affairs throughout Agam Regency with samples taken using the full sampling method totaling 92 samples. The data processing method in this research is the multiple linear regression analysis method. The results of this research show that the variables of apparatus competency, organizational commitment and community participation have a positive but not significant effect on accountability in managing village funds, while transparency has a positive and significant effect on accountability in managing village funds.